Revealing the secrets of Blue Zones - N. Nuray Ulusu; N. Nuray Ulusu (Frontiers in Pharmacology)
Aging is influenced by cellular senescence mechanisms that are associated with oxidative stress. Oxidative stress is the imbalance between antioxidants and free radicals. This imbalance affects enzyme activities and causes mitochondrial dysfunction. It also slows down cellular energy production and disrupts cellular homeostasis. Additionally, oxidative stress stimulates inflammation, increases the number of point mutations, and alters intercellular communication. It can lead to epigenetic alterations, genomic instability, telomere attrition, and loss of proteostasis. Ultimately, these factors contribute to aging and the development of chronic diseases. Glucose-6-phosphate dehydrogenase (G6PD) is an antioxidant enzyme that protects cells from oxidative and nitrosative damage. It helps restore redox balance, preserve macromolecule function, and rescue cells from cellular senescence, autophagy, and stress-induced apoptosis. G6PD is considered an anti-senescence enzyme. The World Health Organization classifies G6PD variants into five groups based on the enzyme’s residual activity. The first four classes are categorized according to the degree of G6PD deficiency, while the fifth class includes variants with enzyme activities greater than normal. Increased G6PD activity does not exhibit clinical manifestations. Consequently, the full spectrum of mutations and the prevalence of increased G6PD activity in the population remain unknown. The world’s oldest and healthiest people live in Blue Zones. These comprise isolated populations, and there may be a geographic prevalence of high-activity G6PD variants that protect against oxidative stress-induced senescence. To uncover the secret of centenarians’ longevity, additional research is needed to determine whether the hidden factor is the increased activity of the G6PD enzyme.